A Systematic Literature Review on the Role of Digital Learning Media in Improving Learning Outcomes - Alfin Fauzan; Muklas Ardiansyah; Jufri; Agung Setiawan Fauzan (Universitas Negeri Padang, 2025)
This literature study critically examines the evolution and utilization of multimedia learning media in modern education, emphasizing the increasing demands for innovative teaching methods that integrate digital technology. As educational paradigms shift towards learner-centered approaches, teachers are required to leverage digital-based learning media to enhance students’ understanding and improve learning outcomes. This study synthesizes findings from twenty recent peer-reviewed articles, providing a comprehensive overview of how digital learning media facilitate effective knowledge delivery and engagement. Unlike traditional tools, digital media offer dynamic, interactive, and accessible learning experiences that align with current technological advancements and educational needs. The analysis reveals key trends, benefits, and challenges in adopting multimedia learning media, highlighting significant opportunities for further development and implementation in diverse learning contexts. This study contributes to the field by consolidating up-to-date evidence on the impact of digital learning media, thereby informing educators, researchers, and policymakers on best practices and future directions in technology-enhanced learning.